Evaluation of Risk Management in Lending Activities by LKM Artha Kerta Raharja - Effendi, Syahrul; Mustika, Maya; Faruqi, Faris; Ramaditya, Muhammad (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2025)
This study aims to provide comprehensive insights into loan disbursement procedures, risk evaluation, and the role of Microfinance Institutions (MFIs) in promoting financial inclusion. A qualitative research method was employed, using observation, interviews, and documentation for data collection. The research was conducted at Artha Kertaraharja Microfinance Institution located in Cikupa, Tangerang Regency, with a focus on evaluating risk management in loan disbursement activities. Data were obtained through structured and semi-structured interviews and document analysis. The findings indicate that Artha Kertaraharja MFI primarily provides microloans and multi-purpose business loans to strengthen working capital, improve living standards, and support regional economic development. The loan disbursement process includes assessing borrower profiles, determining loan amounts, and analyzing owned assets. Risk evaluation plays a crucial role in this process. The MFI applies the Rate Payment Capacity (RPC) method to assess credit risk by calculating borrowers’ net income after household and business expenses to measure repayment ability. Additionally, Artha Kertaraharja MFI implements persuasive, non-coercive collection approaches, offers preventive solutions, and provides credit insurance for borrowers experiencing serious repayment difficulties